Comparison of clinicopathological characteristics and survival outcomes between solitary and multiple rectal neuroendocrine tumors: a propensity score-matched study - Zheng, Ye; Wang, Limei; Guo, Jing; Wang, Peng; Ji, Rui; Liu, Jun (Frontiers in Oncology, 2025)
IntroductionMultiple rectal neuroendocrine tumors (RNETs) are rare rectal malignancies, and there is no consensus on their characteristics and treatments. This study aimed to explore the heterogeneity of key morphological parameters in multiple RNETs and to compare the clinicopathological characteristics between multiple and solitary RNETs.MethodsA total of 15 patients with multiple RNETs and 89 patients with solitary RNETs treated between 2013 and 2024 were retrospectively analyzed using propensity match analysis to determine their clinicopathological characteristics. WHO grade, the expression of basal diagnostic markers (synaptophysin/chromogranin A/CD56), and somatostatin receptor 2 (SSTR2) were analyzed. Disease-free survival rates were calculated using the Kaplan–Meier method.ResultsMultifocal RNETs were characterized by homogeneous WHO grading (93.3%) and concordant SSTR2 expression. The solitary RNETs group had a significantly higher SSTR2 positivity rate (p < 0.05) but significantly lower chromogranin A positivity rate than the multiple RNETs group (p < 0.05).ConclusionMultiple RNETs demonstrate remarkable homogeneity in core diagnostic parameters. However, compared to solitary RNETs, multifocal presentations exhibit a significantly higher propensity for metastasis/recurrence, warranting intensified therapeutic protocols and enhanced clinicopathological surveillance paradigms.